Missing the SDGs: Political accountability for insufficient environmental action - Lena Partzsch (Global Policy, 2023)
The Sustainable Development Goals (SDGs) demonstrate an integration of development and environmental agendas. However, none of the environmental sub-targets, which were due by 2020, were accomplished. Global governance through goal setting requires functioning mechanisms of accountability. Based on a theoretical framework that differentiates between public, private and voluntary logic of accountability, the article illustratively explores accountability mechanisms concerning the UN 2030 Agenda for Sustainable Development. This allows to discuss the untapped potential for holding power wielders, such as governments, private companies, and norm champions, accountable. While the SDGs were adopted within public governance institutions, there are regulative means of accountability available that follow private and voluntary logic. Acknowledging this hybrid character of accountability in the implementation stage, the article concludes that there is a need for additional research to explore dimensions of non-public accountability for goals agreed upon by the international community. SDG indicators should be mandatory for corporate reporting, and civil society organisations should report more comprehensively on the spread of environmental norms in global development.
Keywords: 320